Preclinical Advances in Theranostics for the Different Molecular Subtypes of Breast Cancer - Fang, Hanyi; Cavaliere, Alessandra; Li, Ziqi; Huang, Yiyun; Marquez-Nostra, Bernadette (Frontiers in Pharmacology, 2021)
Breast cancer is the second most common cancer in women worldwide. The heterogeneity of breast cancer and drug resistance to therapies make the diagnosis and treatment difficult. Molecular imaging methods with positron emission tomography (PET) and single-photon emission tomography (SPECT) provide useful tools to diagnose, predict, and monitor the response of therapy, contributing to precision medicine for breast cancer patients. Recently, many efforts have been made to find new targets for breast cancer therapy to overcome resistance to standard of care treatments, giving rise to new therapeutic agents to offer more options for patients with breast cancer. The combination of diagnostic and therapeutic strategies forms the foundation of theranostics. Some of these theranostic agents exhibit high potential to be translated to clinic. In this review, we highlight the most recent advances in theranostics of the different molecular subtypes of breast cancer in preclinical studies.